The Prevalence of Helminthiasis in Bali Cattle in Pamona Puselemba District Poso Regency - Managanta, Andri Amaliel (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Worms in the digestive tract of livestock are generally asymptomatic or chronic. The disease causes economic losses due to decreased body weight and productivity of livestock, and can even cause death. The study aimed to determine the prevalence of helminthic parasitic infections in the digestive tract of Bali cattle in Pamona Puselemba District Poso Regency. This type of research is an experimental laboratory and was carried out from January to December 2021. This study used 77 samples of Bali cattle feces obtained from cattle belonging to the community in Pamona Puselemba District and maintained intensively or extensively. The inspection process used the floating test method and the sedimentation test at the Maros Veterinary Center Laboratory Maros Regency South Sulawesi Province. Based on the results of the study, the prevalence of parasitic worm infection in the digestive tract of Bali cattle in Pamona Puselemba District Poso Regency was 71.45%. The types of worms that infect the digestive tract of Bali cattle include worms Paramphistomum spp, 32.47% and followed by worms Trichostrongylus spp, 5.19%, Strongyloides, spp 2.56%, and Cooperia 2.56%. There are liver flukes or Fasciola that infect 2.56% and are infected with protozoa, namely Eimeria, spp with a prevalence of 3.89%.